Therapeutic Response of Serum Lipids to Atorvastatin in Type II Diabetic Patients - M. Murtadha, Riyadh (Iraqi Journal of Pharmaceutical Sciences, 2017)
Lipid disorders and cardiovascular disease (CVD) risk are known to be increased in patients with diabetes mellitus. The effects of statins on serum lipid levels are well known; however, previous studies did not compare the effects of statins on serum lipid levels in diabetic patients with non-diabetic patients. To investigate the effects of Atorvastatin on serum lipid profiles in hyperlipidemic patients with type 2 diabetes mellitus in comparison with hyperlipidemic patients without diabetes.This study was conducted on 33 type 2 diabetic patients & 34 non-diabetic patients; their age range was 40-80 years, all of them were hyperlipidemic, who had been administered 10, 20, & 40 mg daily of Atorvastatin and completed a 6-month follow-up. Serum lipids were measured before and after treatment at 1, 3, and 6 months.It was found that the reduction in S. Total Cholesterol and S. LDL-C were less in diabetic patients than that in non-diabetic patients when they are using the same doses of Atorvastatin, while the changes in S. HDL-C and S. Triglyceride were nearly similar in both. Furthermore, it is noticed that nearly the same responses of S. Cholesterol and S. LDL-C reduction were achieved in diabetic patients when they are using doubled doses that are used for non-diabetic patients.So,higher doses of Atorvastatin (double doses) are needed to improve serum lipid levels in diabetic patients as compared to non-diabetic patients. Key words: Diabetic , Lipids , Atorvastatin.